Investigation on the Phytochemistry, Antioxidant, and Hepatoprotective Properties of the Ethanolic Extract of Gymnostachyum febrifugum Benth - Lekha Mathew
Background: The phytochemical evaluation of the ethanolic extract of the plant, Gymnostachyum febrifugum Benth. (Acanthaceae family) was carried out to evaluate its therapeutic potential. Despite being part of traditional medicine, not much research has been done on the plant. Materials and Methods: The study aimed to understand the plant$1 (Bs phytochemistry and evaluate its therapeutic potential. For this purpose, DPPH, ABTS, FRAP, Total Antioxidant Assay, MTT Assay, and HR-LCMS techniques were employed. Results: Major secondary metabolites in the ethanolic extract were flavonoids, tannins, phenolics, and steroids. The free radical scavenging capacity of the ethanolic extract of the plant was evaluated using four different methods, proving the plant to possess high antioxidant properties. Hence, the hepatoprotective potential of ethanolic extract was evaluated using an MTT assay on Hep G2 cells induced with hepatotoxicity using Acetaminophen. When treated with ethanolic extract, the cell viability was found to be 85.32% at 12.5 (So(Bg/mL concentration. IC50 for ethanolic extract was attained at 75.77 (So(Bg/mL. Also, chemical characterization of the extract was performed using the HR-LCMS technique. Around 64 compounds were obtained in chromatogram using positive ESI mode, of which 24 are unknown and 40 are known compounds. Out of 37 compounds obtained in the negative ESI mode, 27 were known, and 10 were unknown.s